Analisis Penerimaan Retribusi Pasar Alok Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Sikka (Studi Kasus Pada Dinas Perdagangan, Koperasi Dan UKM) - Kornelia Kristina; Henrikus Herdi; Yoseph Darius Purnama Rangga (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to analyze the level of growth, level of effectiveness and contribution of alok market retribution revenue in increasing the local revenue of Sikka Regency. The method used in this research is a quantitative method. Data collection techniques using observation, interviews and documentation. Data analysis techniques using growth rate analysis, effectiveness level analysis, and contribution analysis. The results of this study indicate that the growth rate of alok market retribution acceptance is classified as unsuccessful with an average of 1.51%, the level of effectiveness of alok market retribution acceptance is classified as less effective with an average of 65.46%, and the contribution of market retribution revenue alok in increasing Sikka regency's own-source revenue is classified in the criteria of very less contribution with an average of 0.05%.